Diagnostic study of interface materials of co-deposition simulating impurity relevant to international thermonuclear experimental reactor by using calibration-free laser-induced breakdown spectroscopy; Spectrochimica Acta Part B: Atomic Spectroscopy; Vol. 194 - Imran M. Muhammad; Znen-hua Hu; Fang Ding; Ding Hongbin; Iqbal M. Muzmmil; Ashfaq J. M. Jaweria; Remnev (Remnyov) G. E. Gennady Efimovich; Guang-Nan Luo (2022, 2022)
Title screen